2019
DOI: 10.1080/21691401.2019.1620252
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of miR-143-3p inhibiting proliferation, migration and invasion of osteosarcoma cells by targeting MAPK7

Abstract: Objective: To investigate the effects of miR-143-3p and MAPK7 on the proliferation, migration, and invasion of U2OS human osteosarcoma (OS) cells. Methods: The expression of miR-143-3p and MAPK7 in U2OS cells were detected by qRT-PCR, and the protein level of MAPK7 was measured by western blot assay. The targeting relationship between miR-143-3p and MAPK7 was predicted by TargetScan and verified by dual luciferase reporter assay. MTT and Transwell assays were used to detect cell viability, migrated cells and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…32 Lu et al confirmed that circ_0021977 inhibited the proliferation, migration, and invasion of colorectal cancer cells. 6 To explore the function of circ_0001721, miR-372-3p and MAPK7, we checked its expression level and found that circ_0001721 was conspicuously upregulated, 15 miR-372-3p was low expressed, 21 and MAPK7 was highly expressed in OS tissues and cells, 24 which was in line with a previous report. Our experimental results showed that the down-regulation of circ_0001721 effectively inhibited tumor occurrence.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…32 Lu et al confirmed that circ_0021977 inhibited the proliferation, migration, and invasion of colorectal cancer cells. 6 To explore the function of circ_0001721, miR-372-3p and MAPK7, we checked its expression level and found that circ_0001721 was conspicuously upregulated, 15 miR-372-3p was low expressed, 21 and MAPK7 was highly expressed in OS tissues and cells, 24 which was in line with a previous report. Our experimental results showed that the down-regulation of circ_0001721 effectively inhibited tumor occurrence.…”
Section: Discussionsupporting
confidence: 85%
“…Related studies showed that MAPK7 was involved in the development of a variety of cancers, including OS. 24 Zhou et al proved that MAPK7 was involved in the proliferation and apoptosis of lung cancer. 25 Dong et al reported that miR-143 regulates the proliferation and migration of osteosarcoma cells through targeting MAPK7.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have shown that miR-143-3p was abnormally expressed in various cancers [22,23]. In melanoma, Panza et al revealed that miR-143-3p was diminished and miR-143-3p elevation impeded melanoma cell growth and motility and induced apoptosis by binding to COX-2 [14].…”
Section: Discussionmentioning
confidence: 99%
“…miR-143-3p, a tumor-suppressor miRNA, was reported to be involved in multiple cancers, including renal cell carcinoma [ 20 ], triple-negative breast cancer [ 21 ], and osteosarcoma [ 22 ]. In OSCC, miR-143 inhibition promotes carcinogenesis and development [ 23 ], and the present results show that miR-143-3p expression is reduced in OSCC tissues and cells.…”
Section: Discussionmentioning
confidence: 99%